Popular cultural representations of postfeminist religiosity in the International Christian Fellowship: an analysis of the "Ladies Lounge 2021" webpage - Freudenberg, Maren (Zeitschrift für Religion, Gesellschaft und Politik, 2021)
Femininity and female gender roles in conservative religious environments are highly disputed topics both within communities of faith and in sociological discourse. In light of social transformations of gender perceptions in the past decades, conservative Christians have had to reevaluate traditional understandings of womanhood in societies that have become steeped in popular culture and thoroughly mediatized. Taking this development as a point of departure, this article examines how femininity is represented in the International Christian Fellowship, particularly on its "Ladies Lounge" webpage. Advertising an annual event geared exclusively towards women, the website’s landing page contains images and text that we examine by means of visual and textual sequence analysis. Our research results reveal that women are depicted as sensually attractive and self-confidently professional while at the same time being relegated to an exclusively female sphere within (but not beyond) which they wield authority and influence. As such, femininity is represented as self-empowering, but only within a specific, postfeminist framework. This ambivalent depiction of women’s agency challenges conservative Evangelical values at the same time as it affirms them. In this sense, the study contributes the growing body of literature on gender and Evangelicalism.